Knowledge of Oral and Dental Health as a Risk Factor for Pulp Disease Among the Elderly - Arofat, Yasir; Isnanto, Isnanto; Mahirawatie, Ida Chairanna (FORIKES, 2026)
Pulp disease is one of the most common oral health problems among the elderly. In recent years, cases of pulp disease among older adults have shown a consistent increase. This condition indicates the need to explore contributing factors, particularly the level of knowledge regarding oral and dental health, which may influence the occurrence and progression of pulp disease in this population. This study aimed to determine the relationship between knowledge of oral and dental health and the incidence of pulp disease among the elderly at Wonosalam Primary Health Center, Jombang Regency. This study employed a cross-sectional design conducted at Wonosalam Primary Health Center, Jombang Regency. The study population consisted of elderly participants selected as research respondents. Data were collected using a structured questionnaire to assess the level of knowledge regarding oral and dental health. The association between knowledge and pulp disease was analyzed using the Chi-Square test. The analysis demonstrated a statistically significant relationship between knowledge of oral and dental health and the occurrence of pulp disease among the elderly (p = 0.03). Participants with lower levels of knowledge were more likely to experience pulp disease compared to those with better knowledge. As conclusion, knowledge of oral and dental health is significantly associated with pulp disease among the elderly. Improving educational and preventive efforts targeting older adults is essential to enhance awareness and reduce the risk of pulp disease.Keywords: knowledge; elderly; pulp disease; oral and dental health